2005
DOI: 10.1238/physica.topical.115a00695
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Temperature Dependence of C60 on Silicon Surfaces Bond Evolution and Fragmentation as Detected by NEXAFS

Abstract: We report a near-edge x-ray absorption spectroscopy (NEXAFS) study of the C K-edge of C 60 molecules interacting with Si(100) and Si(111) surfaces. Annealing the C 60/Si systems at 1050 K induces fullerene fragmentation and leads to SiC nucleation. Tuning the probing depth and studying polarization dependence, the NEXAFS results shed light on the evolution of the molecular states after thermal treatment, up to the fullerene fragmentation and SiC formation. The NEXA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The compositional and quantitative analysis of GNFs and GNFs:Si obtained from XPS analysis is tabulated in Table I. In general, the peak observed at $284.6 eV for GNFs can be assigned as the C-C bond (carbon sp 2 -hybridization), which is shifted to the higher energy at $285.4 eV and became broaden for GNFs:Si having Si/(Si þ C) of 0.35, as clearly shown in Figure 2 Pedio et al 19 studied the dependence of the formation of C60 on silicon surfaces on the annealing temperature using C 1s XPS measurements and found that the C-C bond and C-Si bond features are located at 284.2 and 282.6 eV, respectively. We have observed a peak at $283.3 eV, which is in between the peaks 284.2 and 282.6 eV (films having Si/(Si þ C) ¼ 0.35) as shown in Figure 2(d) and is assigned as C-Si peak.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…The compositional and quantitative analysis of GNFs and GNFs:Si obtained from XPS analysis is tabulated in Table I. In general, the peak observed at $284.6 eV for GNFs can be assigned as the C-C bond (carbon sp 2 -hybridization), which is shifted to the higher energy at $285.4 eV and became broaden for GNFs:Si having Si/(Si þ C) of 0.35, as clearly shown in Figure 2 Pedio et al 19 studied the dependence of the formation of C60 on silicon surfaces on the annealing temperature using C 1s XPS measurements and found that the C-C bond and C-Si bond features are located at 284.2 and 282.6 eV, respectively. We have observed a peak at $283.3 eV, which is in between the peaks 284.2 and 282.6 eV (films having Si/(Si þ C) ¼ 0.35) as shown in Figure 2(d) and is assigned as C-Si peak.…”
Section: Methodsmentioning
confidence: 88%
“…We have observed a peak at $283.3 eV, which is in between the peaks 284.2 and 282.6 eV (films having Si/(Si þ C) ¼ 0.35) as shown in Figure 2(d) and is assigned as C-Si peak. 19,20 The peak observed at $283.9 eV and 284.5 eV in Figures 2(c) and 2(d), respectively, is assigned as C¼C sp 2 , whereas the peak 285.0 eV and 285.6 eV in Figures 2(c) and 2(d), respectively, is defined as "defect peaks" 16 or Si-C-O bonding peaks. 21 The peak observed in Figure 2(c) at 286.8 eV is the C-O bonds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak observed at ∼284.4 eV for GNFs can be assigned as the C-C bond, which is shifted to the higher energy at ∼285.2 eV and became broader for GNFs:Si. Pedio et al 21 studied the dependence of the formation of C 60 on silicon surfaces on the annealing temperature using C 1s XPS measurements and found that the C-C bond and C-Si bond features are located at 284.2 and 282.6 eV, respectively. In the present case, the spectral features are different and do not have the signature of SiC segregations in C 1s core-level XPS spectra, which further confirms enhanced sp 3 bonding (i.e., diamond and/ or diamond-like carbon) rather than sp 2 bonding (like graphite and/or CNTs) and/or C-Si bonding.…”
Section: Resultsmentioning
confidence: 99%
“…The C 1s peak of oxidized Si-NPs decorated MWCNTs shifts towards a lower energy, significantly indicating the formation of sp 3 -rich material. The deconvoluted C 1s XPS peaks of MWCNTs/SiO 2 -NP (Si-NPs = 5.75 atom %) nanocomposites are observed at ∼281.8 and ∼282.4 eV which are strong indicators of the C–Si bonds, 37 and confirm the formation of MWCNTs/SiO 2 -NP nanocomposites.…”
Section: Resultsmentioning
confidence: 74%